Methylene tetrahydrofolate reductase genotype modifies the chemopreventive effect of folate in colorectal adenoma, but not colorectal cancer. - Lightfoot, T; Barrett, J; Bishop, T; Northwood, E; Smith, G; Wilkie, M; Steele, R; Carey, F; Key, T; Wolf, R; Forman, D (2008)
Epidemiologic evidence suggests a role for folate, a critical component of the 1-carbon cycle, in colorectal adenoma and cancer pathogenesis. Low folate levels, along with genetic polymorphisms in key enzymes such as methylene tetrahydrofolate reductase (MTHFR), can cause DNA hypomethylation and aberrant CpG methylation, which have been associated with colorectal tumor development. We investigated self-reported folate and alcohol intake alongside possible modifying effects of MTHFR 677 C>T and 1298 A>C polymorphisms in UK case-control studies of colorectal adenoma (317 cases, 296 controls) and cancer (500 cases, 742 controls). A significant association between MTHFR 1298 and colorectal cancer risk was observed [odds ratio, 1.57; 95% confidence interval (95% CI), 1.05-2.37], which was more pronounced in males (odds ratio, 3.02; 95% CI, 1.63-5.62). Although we found no association between MTHFR 677 and colorectal cancer, when data were stratified by sex, an increased risk was seen in females (odds ratio, 1.96; 95% CI, 1.11-3.46) but not in males. High folate intake was associated with a decreased risk for colorectal adenoma (odds ratio, 0.47; 95% CI, 0.30-0.73; P(trend), <0.001), which was modified by MTHFR 1298 genotype (P(interaction) = 0.006). However, we found no evidence to support the hypothesis that a high-folate diet protects against colorectal cancer development. Consistent with previous studies, high alcohol intake (>or=14 U/wk) was associated with a significantly increased cancer risk (odds ratio, 2.57; 95% CI, 1.81-3.64). Our data suggest that dietary folate intake may be an important determinant for premalignant colorectal disease development but not colorectal cancer, an association that is modified by MTHFR genotype.